Yam bean oleoresin and seed quality of common bean infested by Acanthoscelides obtectus Say. - Rangel-Lucio, José Antonio (2011)
The objective of this investigation was to evaluate the effect of yam bean oleoresin on common bean seed quality and bean weevil control. The oleoresin extract was obtained by the HPLC technique, the presence of rotenone was detected(15 mg/l). Three concentrations of oleoresin extract were tested (Ci, g/ml): C1 (5x10-7, 5x10-6, …5x10-2); C2 (1x10-2, 2x10-2,…6x10-2); C3 (5x10-1, 6x10-1,…9x10-1) and one control treatment per concentration, applied to recipients of 300 ml with 50 g of common bean (varieties Flor de Mayo, Flor de Junio, Mayocoba) and 20 adults bean weevils inside. The bioassay only utilized common beans treated with the C2 concentration by 48 h to evaluate seed vigor and standard germination of common bean at three and seven days after planted, according to ISTA rules. The results demostrated the common bean normal seedlings and standard germination at five days were provocated by gradual C2 increased,particulary 3 x 10-2 to 6 x 10-2 dilutions at nine days after planted and its confirmed the common bean standard germination.